2012
DOI: 10.1200/jco.2012.30.18_suppl.lba7507
|View full text |Cite
|
Sign up to set email alerts
|

PARAMOUNT: Final overall survival (OS) results of the phase III study of maintenance pemetrexed (pem) plus best supportive care (BSC) versus placebo (plb) plus BSC immediately following induction treatment with pem plus cisplatin (cis) for advanced nonsquamous (NS) non-small cell lung cancer (NSCLC).

Abstract: LBA7507 Background: The PARAMOUNT trial showed that pem continuation maintenance therapy significantly reduced the risk of disease progression over plb (HR=0.62; 95% CI: 0.49-0.79; p <0.0001) in patients (pts) with advanced NS NSCLC who had not progressed during pem-cis induction. Here we present the final OS data. Methods: In a double-blind, plb-controlled study, alpha-controlled for OS, 939 pts received induction (4 cycles of pem 500 mg/m2 and cis 75 mg/m2 on d1 of 21d cycles), and 539 pts who had not pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 0 publications
1
31
0
Order By: Relevance
“…The hazard ratio for PFS is in the range of 0.6 to 0.7 in most of the trials for both strategies. OS is only significantly improved in the SATURN (Cappuzzo et al, 2010) andJMEN (Ciuleanu et al, 2009) switchmaintenance trials, and in the PARAMOUNT trial (Paz- Ares et al, 2012) with the continuation strategy. These were the only three trials with a reasonable size (539 to 889 patients) to enable adequately powered comparisons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hazard ratio for PFS is in the range of 0.6 to 0.7 in most of the trials for both strategies. OS is only significantly improved in the SATURN (Cappuzzo et al, 2010) andJMEN (Ciuleanu et al, 2009) switchmaintenance trials, and in the PARAMOUNT trial (Paz- Ares et al, 2012) with the continuation strategy. These were the only three trials with a reasonable size (539 to 889 patients) to enable adequately powered comparisons.…”
Section: Discussionmentioning
confidence: 99%
“…The PARAMOUNT trial revealed that pemetrexed maintenance therapy could improve efficacy over placebo following four courses of cisplatin/pemetrexed (Paz- Ares et al, 2011). The primary objective of this study, PFS, was improved in the pemetrexed maintenance arm compared with placebo (4.1 vs. 2.8 months, HR 0.62), and OS was also significantly improved (13.9 vs. 11 months, HR 0.78) (Paz- Ares et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In the last decades, the interest in lung cancer and pleural mesothelioma has rapidly increased. Lung cancer is currently the deadliest cancer [5], but there have been considerable advances in the diagnosis and treatment of this disease that has led to an improvement of median survival in advanced-stage lung cancers from 7-8 months in 2000 [6] to 15 months in 2010 [7]. The incidence of mesothelioma is still increasing worldwide [8].…”
Section: @Erspublicationsmentioning
confidence: 99%
“…The significant pfs that was observed did not translate into an os benefit (os being the primary endpoint of the trial), nor was qol improved. More recent practice-changing clinical trials supporting maintenance systemic treatments after a platinum doublet have used pfs as the primary endpoint (Table iii) [46][47][48][49] . Pemetrexed has been studied in the jmen and paramount trials, and erlotinib in the saturn trial, as maintenance after platinum doublet, and both a pfs and an os benefit have been reported, suggesting a correlation [46][47][48][49] .…”
Section: Pfs As a Surrogate For The Os Endpoint Inmentioning
confidence: 99%
“…More recent practice-changing clinical trials supporting maintenance systemic treatments after a platinum doublet have used pfs as the primary endpoint (Table iii) [46][47][48][49] . Pemetrexed has been studied in the jmen and paramount trials, and erlotinib in the saturn trial, as maintenance after platinum doublet, and both a pfs and an os benefit have been reported, suggesting a correlation [46][47][48][49] . Docetaxel, pemetrexed, and erlotinib are all agents that have shown a pfs and os benefit in the second-line setting, and thus it is not surprising that, compared with best supportive care, giving active drug earlier delays progression as has been reported 18,[38][39][40] .…”
Section: Pfs As a Surrogate For The Os Endpoint Inmentioning
confidence: 99%